Understanding pharmaceutical sustainable supply chains – a case study application - Bravo, A. M.; Crespo de Carvalho, J. (Independent Journal of Management and Production, 2013)
A major paradigm change is occurring in the pharmaceutical industry and an increase of returnsand recalls has been seen; although this industry in known for the continuoussearch for quality and regulatory compliance.Hence, in this paperwe combine the findings of previous literature reviews conducted by theauthors. Essentially, explore the links between pharmaceutical drugs quality,reverse logistics, and sustainability. A case study on a global corporation manufacturing in the area of generic drug products has been selected andcorrelations are done with regards to returns and recalls from hospitalpharmacies, in particular. With this approach it is expected to link bothparties in the application of a quality by design risk management approach aswell as reduce variability and risk of noncompliance.